2020
DOI: 10.2478/bjdm-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

The role of Helicobacter pylori in development of lesion in oral cavity

Abstract: SummaryBackground/Aim: to examine the connection of H. Pylori in saliva and biopsy material with oral lesions.Material and Methods: Sixty patients with dyspeptic complaints were followed up at the Clinic for Gastroenterology at University Medical Clinical Centre in Skopje, divided into two groups: first group consisted of 30 patients without presence of H. pylori, and the second group with 30 subjects and presence of H. pylori. The presence or absence of H. pylori has been ascertained after endoscopic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There have been several studies conducted in the past that have suggested for the involvement of various bacterial and fungal infections for inflammation and irritation of the oral mucosa and gastrointestinal mucosa 9,10 . Helicobacter pylori have been liked with the development of various oral mucosal lesions including lingual papillary hyperplasia 11 . Similary, Helicobacter pylori ( H. pylori ) could also be associated with the development of IPH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been several studies conducted in the past that have suggested for the involvement of various bacterial and fungal infections for inflammation and irritation of the oral mucosa and gastrointestinal mucosa 9,10 . Helicobacter pylori have been liked with the development of various oral mucosal lesions including lingual papillary hyperplasia 11 . Similary, Helicobacter pylori ( H. pylori ) could also be associated with the development of IPH.…”
Section: Discussionmentioning
confidence: 98%
“…9 , 10 Helicobacter pylori have been liked with the development of various oral mucosal lesions including lingual papillary hyperplasia. 11 Similary, Helicobacter pylori ( H. pylori ) could also be associated with the development of IPH. In multiple studies by M Cześnikiewicz‐Guzik et.…”
Section: Discussionmentioning
confidence: 99%